RESTRUKTURISASI HUTANG DAN KINERJA KEUANGAN DENGAN PENDEKATAN ANALISIS DISKRIMINAN - Fitri Indah Sari (Jurnal Bisnis dan Kewirausahaan, 2017)
This study aims to evaluate the restructuring of the company in an effort to improve the company's financial performance and to find out how the financial performance MNO (Persero) after restructuring. This study uses qualitative descriptive analysis and financial statement analysis method to measure a company's financial performance over the last five years (2009-2014). Initially analyzed descriptively, it is intended to explain the phenomena that occur in PT MNO Makassar, further financial analysis is intended to measure capital structure and financial performance of companies, using financial ratios that are relevant, then do a comparative analysis, in it is being compared is between financial performance before restructuring and financial performance after the debt restructuring is done. The results showed that before the restructuring was held in the year 2009-2014, the company's financial performance looks very bad, which is marked by several indicators ratio experienced a sharp decline and even negative. But once held the restructuring, (2013-2014) began to increase slightly although the increase is not able to guarantee safe for creditors and owners of the company. Thus, it can be said that the restructuring undertaken by PT MNO to debt management company in 2013, has a positive influence on the financial performance of the company.